Analisis Konstruksi Kausatif Verbal Dialek Batak Toba Di Kabupaten Bungo Provinsi Jambi - Asridayani Asridayani (Krinok:Jurnal Linguistik Budaya, 2017)
The purpose of this research is to describe the verbal construction of Batak Toba Dialect in Bungo Regency Province of Jambi. In collecting the data, the researcher used conversational and listening method. Meanwhile, the main technique in collecting the data is elicitation technique, which is continued by several techniques, i.e. recording technique and taking note. The main technique in observation method is Participant Observation Method (SLC) which is continued by advanced note taking technique. In analyzing the data, the research is done by using substitutional method, translational method, and referential method. The results of the analysis are provided by formal and informal methods.            The result of the research shows that Batak Toba Dialect in Bungo Regency Province of Jambi almost same as Batak Toba Languange in Province of Sumatera Utara which can be causative (1) the intransitive verbs by adding the suffix -hon, (2) the intransitive verbs by adding the suffix -i if the predicate is an adjective, and (3) the transitive verbs, intransitive verbs, and precategorial by adding the prefix pa-. BTL can also aplicativise some verbs by adding the suffix -hon and the suffix -i. The resultative construction of BTL marked by prefix -di‘di’ and prefix -tar ‘ter’ Keywords: Batak Toba Dialect, Causative.